1998
DOI: 10.1002/1529-0131(199809)41:9<1552::aid-art5>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic efficacy of multiple intravenous infusions of anti-tumor necrosis factor ? monoclonal antibody combined with low-dose weekly methotrexate in rheumatoid arthritis

Abstract: Multiple infusions of cA2 were effective and well tolerated, with the best results occurring at 3 and 10 mg/kg either alone or in combination with MTX in approximately 60% of patients with active RA despite therapy with low-dose MTX. When cA2 at 1 mg/kg was given with low-dose MTX, synergy was observed. The results of the trial provide a strategy for further evaluation of the efficacy and safety of longer-term treatment with cA2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
748
7
52

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 1,508 publications
(836 citation statements)
references
References 32 publications
29
748
7
52
Order By: Relevance
“…All patients had longstanding RA fulfilling the 1987 revised criteria of the American College of Rheumatology (ACR; formerly, the American Rheumatism Association) (7). Initially, these patients were included in multicenter, double-blind, placebocontrolled, randomized anti-TNF antibody studies (8,9). From those studies, clinical data and patient samples were available in order to retrospectively study aspects of the endocrine system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients had longstanding RA fulfilling the 1987 revised criteria of the American College of Rheumatology (ACR; formerly, the American Rheumatism Association) (7). Initially, these patients were included in multicenter, double-blind, placebocontrolled, randomized anti-TNF antibody studies (8,9). From those studies, clinical data and patient samples were available in order to retrospectively study aspects of the endocrine system.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical improvement was calculated according to the following formula: improvement (%) ϭ 100 ϫ (1 -[DAS28 followup /DAS28 baseline ]), where DAS28 ϭ Disease Activity Score in 28 joints (10). For both types of anti-TNF antibodies, detailed efficacy assessments including ACR and European League Against Rheumatism response criteria have been reported elsewhere, and they are not reported here (8,9).…”
Section: Methodsmentioning
confidence: 99%
“…Another approach to addressing the need for MTX in the combination would be to gradually withdraw the MTX in a blinded manner once an optimal response of the DMARD combination has been achieved. Unfortunately, no studies of MTX withdrawal have been published to date, with the exception of a trial with a biologic agent (37). Taken together, the efficacy of the combination of cyclosporine or leflunomide with MTX or with SSZ may reflect the efficacy of the DMARD add-on alone, as supported by the remarkably similar efficacy of monotherapy and combination strategies with cyclosporine or leflunomide ( Table 1).…”
Section: Study Design Issuesmentioning
confidence: 99%
“…As mentioned above, although the results have uniformly demonstrated substantial benefit of the combination arm, the failure of most trials to include an arm with the biologic alone calls into question the utility of the combination. In a trial of infliximab in patients with active disease despite MTX therapy, in which MTX was partly withdrawn, there was a clear trend toward better efficacy of the combination compared with the biologic monotherapy, which was partly interpreted as being due to increased immunogenicity of the biologic in the absence of MTX (37). The effect of MTX in combination with monoclonal anti-TNF antibodies has been interpreted as a reduction in the immunogenicity of the monoclonal agent.…”
Section: Study Design Issuesmentioning
confidence: 99%
“…Because initial safety studies suggested no increase in adverse hematologic events, current guidelines do not recommend regular complete blood cell count (CBC) monitoring for anti-TNF therapy (2)(3)(4)(5). However, significant hematologic reactions, in particular neu-tropenia, have been reported in patients treated with all 3 TNF inhibitor agents (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%